Truth : a guide - Blackburn, Simon, 1944- (Oxford ; New York : Oxford University Press, 2005)
Blackburn is an eminent thinker who is able to explain philosophy to the general reader. Now he offers an exploration of what he calls "the most exciting and engaging issue in the whole of philosophy"--The age-old war over truth. The front lines are well defined: on one side are those who believe in plain facts, rock-solid truths that can be found through reason and objectivity--that science leads to truth, for instance. Their opponents see the dark forces of language, culture, power, gender, class, ideology and desire--all subverting our perceptions of the world, and clouding our judgment with false notions of absolutes. Beginning with an early skirmish--when Socrates confronted the sophists in ancient Athens--Blackburn offers a penetrating look at the longstanding battle. Among the questions he considers are: is science mere opinion, can historians understand another historical period, and indeed can one culture ever truly understand another.--From publisher description
Faith, belief, and reason -- Man the measure -- Ishmael's problem and the delights of keeping quiet -- Nietzsche : the arch debunker -- The possibility of philosophy -- Observation and truth : from Locke to Rorty -- Realism as science; realism about science -- Historians and others
Includes bibliographical references (pages 223-234) and index
Keywords: Truth